2008
DOI: 10.1364/oe.16.010549
|View full text |Cite
|
Sign up to set email alerts
|

GaN nanorod light emitting diode arrays with a nearly constant electroluminescent peak wavelength

Abstract: A practical process to fabricate InGaN/GaN multiple quantum well light emitting diodes (LEDs) with a self-organized nanorod structure is demonstrated. The nanorod array is realized by using nature lithography of surface patterned silica spheres followed by dry etching. A layer of spin-on-glass (SOG), which intervening the rod spacing, serves the purpose of electric isolation to each of the parallel nanorod LED units. The electroluminescence peak wavelengths of the nanorod LEDs nearly remain as constant for an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 18 publications
2
50
0
Order By: Relevance
“…The silica spheres allow for simple large area patterning, obviating the need for more expensive lithographic techniques. In contrast to recently reported work also employing nanospheres to plasma etch nanorod LEDs 22 , the dry etch in our process is then followed by a wet chemical (KOH-based) etch of the nanorod sidewalls. The wet etch rate is facet dependent for GaN, leading to hexagonally-shaped nanorods with nonpolar m-plane sidewalls, as shown in Figure 7a.…”
Section: Nanowire Templated Lateral Epitaxial Growthmentioning
confidence: 95%
“…The silica spheres allow for simple large area patterning, obviating the need for more expensive lithographic techniques. In contrast to recently reported work also employing nanospheres to plasma etch nanorod LEDs 22 , the dry etch in our process is then followed by a wet chemical (KOH-based) etch of the nanorod sidewalls. The wet etch rate is facet dependent for GaN, leading to hexagonally-shaped nanorods with nonpolar m-plane sidewalls, as shown in Figure 7a.…”
Section: Nanowire Templated Lateral Epitaxial Growthmentioning
confidence: 95%
“…Several solutions have been proposed, including the insertion of spin-on glass (SOG) as the space layer with rod tips exposed by RIE [12], oblique indium tin oxide (ITO) [13], and the photo-enhanced chemical (PEC) wet oxide process. However, these approaches are not practical due to the high leakage current under reversed bias.…”
Section: Fabrication Of Nanorod Ledmentioning
confidence: 99%
“…However, these approaches are not practical due to the high leakage current under reversed bias. Some works have reported a reduction of the reverse bias current to the μA range [12,14,15]. The optical power of GaN-based nanorod arrays is as high as 3700 mW/cm 2 at an injection current of 20 mA [7].…”
Section: Fabrication Of Nanorod Ledmentioning
confidence: 99%
See 1 more Smart Citation
“…We are furthermore interested in the possibility to modulate strain and piezoelectric polarization by post growth patterning. It has been demonstrated that nanorod LEDs can eliminate the conventional blue shift with increasing current by reducing strain [2] and quantum dot LEDs show a reduced droop [3]. This work looks at the mesa size dependence of electroluminescence (EL) and establishes an experimental framework for the investigation of droop in nano-sized LEDs.…”
mentioning
confidence: 97%